The 'fit' between forward-looking activities and the innovation policy governance sub-system: A framework to explore potential impacts - Attila Havas; K. Matthias Weber (Hungarian Academy of Sciences, Institute of Economics, 2016)
Forward-looking activities (FLAs) can influence innovation systems in various ways to a significant extent. This paper focuses on changes induced by FLAs in the innovation policy governance sub-systems (IPGSs) of the national innovation system (NIS). Our knowledge is surprisingly limited even on this subset of FLA impacts, despite several decades of practice and non-negligible analytical efforts. We propose new taxonomies of FLAs and IPGSs and explore hypotheses on the likely 'fit' between different types of FLAs and various IPGSs. Countries selected to illustrate the relevance of our analytical framework include Germany, Greece, and Hungary. Our intention is contribute to a more refined theory building concerning the role and likely impacts of FLAs. Further, as a better understanding of impacts supports the design of more appropriate and effective FLAs, as well as more insightful evaluation of FLAs, this approach is of practical relevance, too.
Keywords: B52; O30; O38; O39; 330; Forward-looking activities (FLAs); Impacts of FLAs; STI policy governance sub-systems; Tentative taxonomies